Evaluation of chickpea (Cicer arietinum L.) in response to salinity stress - Sobh, Mawia; Zargar, Tahoora Batool; Basal, Oqba; Veres, Szilvia (Acta Agraria Debreceniensis, 2023)
Soil salinity is a severe and expanding soil degradation problem that affects 80 million ha of arable lands globally. Chickpea (Cicer arietinum L.) is very sensitive to saline conditions; the most susceptible genotypes may die in just 25 mM NaCl in hydroponics. Approximately 8–10% yield loss in chickpea production is estimated due to salinity stress. However, it is still not established why chickpea is so susceptible to salt affection. Salinity (NaCl) impedes germination of seeds, though chickpea varieties considerably differ from one another in this respect. Some chickpea genotypes are more tolerant in the stage of germination, tolerating even 320 mM NaCl. The reasons of this variation are unrevealed; there is a shortage of knowledge about the germination abilities of chickpea genotypes in saline conditions. Nevertheless, the effect of salt stress on vegetative growth can be analysed in hydroponics, in pot or field conditions, regardless the experimental environment, the ranking of genotypes regarding salt resistance is coherent. Chickpea genotypes can be different in their ability to retain water, maybe under salt affection; the more salt tolerant lines can maintain higher water content in the shoots, while the more sensitive ones cannot. The identification of salt tolerant chickpea landraces based on developing genetic variability is a suitable strategy to combat against salinity problems arising in arid and semi-arid areas.